2013
DOI: 10.1108/s1746-9791(2013)0000009008
|View full text |Cite
|
Sign up to set email alerts
|

Putting the Emotion Back: Exploring the Role of Emotion in Disengagement

Abstract: This chapter explores the nature of disengagement and the role played by emotions and in doing so will disentangle the overlapping theories and definitions of both engagement and disengagement. The research that forms the basis for the chapter comes from two related studies exploring engagement and disengagement in 10 large UK public and private sector organisations. Both studies used an interpretive approach involving 75 managers and employees. The chapter suggests the that emotions play a mediating role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…In line with earlier studies (Fujiwara et al, 2003;Kahn, 1990;Parkinson & McBain, 2013), actor conflict was only related to actor disengagement and not to actor exhaustion, and indeed suggests that conflict is more likely to be related to the attitudinal aspect of burnout than to the physical aspect of burnout. However, given that workload also related to disengagement suggests that more research is needed to be able to reach firm conclusions about the potentially differential relationships of job characteristics such as workload and interpersonal conflict with specific aspects of burnout.…”
Section: Theoretical Contributionssupporting
confidence: 89%
See 1 more Smart Citation
“…In line with earlier studies (Fujiwara et al, 2003;Kahn, 1990;Parkinson & McBain, 2013), actor conflict was only related to actor disengagement and not to actor exhaustion, and indeed suggests that conflict is more likely to be related to the attitudinal aspect of burnout than to the physical aspect of burnout. However, given that workload also related to disengagement suggests that more research is needed to be able to reach firm conclusions about the potentially differential relationships of job characteristics such as workload and interpersonal conflict with specific aspects of burnout.…”
Section: Theoretical Contributionssupporting
confidence: 89%
“…Exhaustion then arises from the unmanageable workload (Leiter & Maslach, 2009). Disengagement is often associated with interpersonal conflict (Kahn, 1990;Parkinson & McBain, 2013). Intense negative emotions resulting from being in conflict with colleagues (Jehn & Mannix, 2001) may explain the positive relationship between conflict at work and the tendency of employees to disengage from their work.…”
Section: Decreasing Hindering Job Demands and Colleague Well-beingmentioning
confidence: 99%
“…These results highlight the need to analyze not only the negative side of wellbeing, but also the positive aspects, in order to enrich our knowledge because, as this study shows, some variables differentially affect the positive vs. negative sides of wellbeing. Consistent with this, Parkinson and McBain (2013) found that disengagement is not simply the opposite of organizational engagement. Moreover, Fredrickson (2003) argues that positivity does far more than just indicate the absence of the negative (such as fear or threats).…”
Section: Discussionsupporting
confidence: 52%
“…Workload is also often studied in relation to exhaustion and disengagement because of the increased effort that is needed when employees have the feeling that they need to do more at work. Disengagement, thus, is often related to interpersonal conflicts [28,29]. Intense negative emotions derived from being in conflict with colleagues [30] can explain the relationship between conflict at work and the tendency of employees to disengage from their work.…”
Section: The Moderating Role Of Individual Adaptability In the Relatimentioning
confidence: 99%